Introduction to computer and network security : navigating shades of gray - Brooks, R. R. (Richard R.) (Boca Raton, Fl. : CRC Press, 2014)
'This text provides a classroom-tested, practical introduction to software design and implementation, cryptographic tools, and networking issues while addressing social, economic, and political implications. It covers cutting-edge topics, such as wireless security and attacks on websites, privacy and digital rights management, and recent work on security and economics. The text includes hands-on projects to help students better understand how computers and networks function. It also contains a number of case studies and discussion points'--
Includes bibliographical references (pages 255- 288) and index.
Keywords: Computer security; Computer networks -- Security measures; Data protection; Data encryption (Computer science)